Exposure to Abusive and Supporting Environments and Empathy in Portuguese Adolescents - Carvalho Martins, Daniela Mariana; Simões, Alice Margarida; Carvalho Relva, Inês (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2020)
The present investigation aims to analyze an association between exposure to abusive / supportive environments and empathy; explore how differences between exposures in abusive / supportive environments and empathy in terms of sociodemographic variables (gender, age of adolescents and whether or not they have siblings). A sample was altered by 728 Portuguese adolescents aged between 12 and 20 years. In the data collection, the Brief Version of the Basic Empathy Scale (BES-A) inventory, exposure to abusive environments and support to the parents' inventory (EASE-PI) and a sociodemographic questionnaire were applied. This investigation emphasizes the importance of health and education professionals, as an effective way to reduce cases of exposure to abusive environments, enabling the creation of preventive measures.